Impact of ICTs on event management and marketing - Birdir, Kemal; Birdir, Sevda, 1969-; Dalgic, Ali, 1987-; Toksoz, Derya, 1990- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2021)
"This book explores the impact of new information and communications technologies on event management and marketing"--